Smart eco drain cover / Muhammad Amirul Faiz Nordin and Hasni Suryani Mat Hasan - Nordin, Muhammad Amirul Faiz; Mat Hasan, Hasni Suryani (2023)
Urban areas are particularly vulnerable to flash floods, and traditional metal drain covers play a crucial role in controlling stormwater runoff. Unfortunately, the rising incidents of drain cover thefts, driven by the desire to obtain their precious metal content, have caused grave worries. This not only results in financial losses for towns but also poses significant dangers to pedestrians and drivers. As such, this study suggests a novel approach to address this problem: replacing metal drain covers with ones made from concrete and coconut husk. This initiative aims to prevent theft and lessen accidents in the event of flash floods. The study looks on the viability and efficiency of using coconut husk as a more environmentally friendly alternative material for drain covers. Coconut husk fibre is an excellent choice for concrete mix reinforcement due to its high tensile strength and endurance. The goal of the study is to produce a sturdy and resilient drain cover that can endure high traffic volumes and adverse weather conditions by optimising the mix ratio. Laboratory tests were conducted to evaluate the mechanical characteristics and structural soundness of the concrete-coconut husk drain covers.